Recombinant factor VIIa partially reverses the inhibitory effect of fondaparinux on thrombin generation after tissue factor activation in platelet rich plasma and whole blood - Gerotziafas, Grigoris T.; Depasse, François; Chakroun, Tahar; Samama, Meyer M.; Elalamy, Ismail (Thrombosis and Haemostasis, 2004)
Fondaparinux (Arixtra®), a specific AT-dependent FXa inhibitor, is effective and safe in the prevention and treatment of venous thromboembolism, but some major hemorrhagic events may occur. No specific antidote to fondaparinux has been proposed. Recombinant FVIIa (Novoseven®) could be used as an haemostatic treatment, but this option has not been well documented. We studied the effect of rFVIIa (1 µg/ml) on the inhibition of thrombin generation induced by fondaparinux (0.1µg/ml to 1 µg/ml). Coagulation was triggered in platelet rich plasma (PRP) or in whole blood by recalcification in the presence of diluted thromboplastin. In PRP thrombin generation was assessed using the thrombinoscope assay. In whole blood, prothrombin activation was assessed by measuring the kinetics of F1+2 formation using an ELISA assay. Fondaparinux at concentrations equal or greater than 0.5 µg/ml prolonged the initiation phase of thrombin generation, and reduced the velocity of prothrombin activation. It also decreased by 60% the endogenous thrombin potential. In the presence of fondaparinux (0.5 µg/ml to 1 µg/ml) rFVIIa accelerated the initiation phase of thrombin generation, but it did not significantly increase the endogenous thrombin potential. However, rFVIIa did not completely reverse the inhibitory effect of fondaparinux on the parameters of thrombin generation and prothrombin activation. This study shows that rFVIIa accelerates thrombin generation, but does not completely reverse the inhibitory effect of fondaparinux on thrombin generation. The potential clinical use of rFVIIa as haemostatic treatment of major bleedings related to fondaparinux has to be evaluated.
Keywords: Pentasaccharide; fondaparinux; thrombin generation; novoseven; tissue factor